EFISIENSI USAHATANI CABAI RAWIT DI DESA BOCEK KECAMATAN KARANGPLOSO KABUPATEN MALANG - Indasari, Felania Sri; Asnah, Asnah; Kholil, A Yusuf (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
This research aims to analyze the production factors that influence the production of cayenne pepper and see the level of efficiency in the use of production inputs in cayenne pepper farming in Bocek Village, Karangploso District, Malang Regency. The data analysis method used in this research to determine the effect of using production factors in cayenne pepper farming is Cobb Douglas model analysis. The research results show that cayenne pepper farming in Bocek Village uses production inputs simultaneously and influences the production of cayenne pepper. Partially, the use of land area input, NPK fertilizer and KCl fertilizer has an effect on cayenne pepper production in Bocek Village. Meanwhile, the variables of seeds, manure, pesticides and labor have no partial effect on cayenne pepper production in Bocek Village. Technically the use of each Input variable is inefficient. Allocatively, the use of input variables such as land area, seeds, manure, pesticides and labor has a value 1, meaning the use of production factors is inefficient. Meanwhile, NPK fertilizer and KCl fertilizer have a value of 1, meaning that the use of production factors is not allocatively efficient. Economically, the use of input variables such as land area, seeds, manure, pesticides and labor is inefficient and the variables NPK fertilizer and KCl fertilizer are not economically efficient.